The Invisible Perpetrator of Inequality: Modern Conceptualizations of Social Class and Adult Education - Kimeka Campbell (Adult Education Research Conference, 2012)
This paper discusses modern conceptualizations of social class stratification in United States adult education. This paper presents Cultural Historical Activity Theory as an analytical tool to elucidate the increasingly over-stratified and invisible nature of social class in the United States. Keywords: Adult Education, social class, United States, socioeconomic status, cultural historical activity theory.
Keywords: Adult Education; social class; United States; socioeconomic status; cultural historical activity theory